Prevalence and related factors of postpartum depression among jordanian mothers with a history of COVID-19 during pregnancy or after childbirth in a developing country - Shereen Hamadneh; Jehan Hamadneh; Asem Abdalrahim; Mohammed ALBashtawy; Mohammad Suliman; Main Alolayaan; Abdullah Alkhawaldeh (Wolters Kluwer Medknow Publications, 2024)
Background: The magnitude of postpartum depression in Jordan during the COVID-19 pandemic is under-documented, and little is known about its potential social, demographic, and clinical correlates. This study aimed to explore the prevalence and related factors of postpartum depression among Jordanian mothers with a history of COVID-19 during pregnancy or after childbirth. Materials and Methods: This cross-sectional descriptive study was carried out in March-June 2021 among a convenient sample of 109 women with a history of COVID-19 during pregnancy or after childbirth, who were at a leading hospital equipped to care for COVID-19 cases in North Jordan. An online survey using the Edinburgh Postnatal Depression Scale (EPDS) was used to collect information from mothers with a history of COVID-19-positive tests. Results: Among the total number of women who participated in the study (n = 109), 73 women had postpartum depression. The prevalence of postpartum depression in the present study was 67%. In addition, the study found a positive statistically significant correlation between EPDS scores and being a smoker, delivery method, experiencing severe COVID-19 symptoms, and being hospitalized. Conclusions: During the COVID-19 pandemic, women had a high level of postpartum depression. It would be necessary to follow further the confirmed cases of COVID-19, and mothers should be screened for depressive symptoms during pregnancy and followed up for antenatal and postnatal care.